Power Relations and Structural Inequality in Late-Life Divorce: A Socio-Legal Analysis of the Palembang Islamic Court Decisions in 2022 - Ellis Lindini Putri; Ari Azhari; Rahmat Abdullah; Muhammad Husni (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
The increasing incidence of divorce among older couples signifies a notable shift in both the social structure and the legal framework of family law in Indonesia. While long-term marriages are typically associated with emotional stability and strong commitment, data from the Palembang Islamic Court indicate that individuals aged 56 and older remain susceptible to marital dissolution. This article aims to analyze the typology of causes behind late-life divorce and examine the legal reasoning employed by Muslim judges in adjudicating such cases. Adopting a socio-legal approach, the study integrates empirical data with a jurisprudential analysis of 56 divorce decisions issued by the Palembang Islamic Court in 2022. The findings reveal that late-life divorce does not occur abruptly; rather, it is the culmination of long-standing, structurally embedded conflicts, including domestic violence, economic subordination, and inequality in emotional and sexual relations. Furthermore, the study demonstrates that the judicial reasoning of Muslim judges is not entirely neutral; it reflects the internalization of prevailing social norms and institutionalized power relations within the adjudicative process. Accordingly, this article argues that late-life divorce should not be perceived merely as a personal failure but as a manifestation of gender-based structural inequality operating across two primary domains: the domestic and the institutional. Thus, the study calls for a reformulation of Islamic legal approaches and the development of a more gender-responsive religious court system capable of addressing structural disparities in the context of elderly divorce. [Fenomena meningkatnya angka perceraian pada pasangan usia lanjut menandai pergeseran penting dalam struktur sosial dan konfigurasi hukum keluarga di Indonesia. Meskipun pernikahan jangka panjang sering diasosiasikan dengan stabilitas emosional dan komitmen yang kuat, data dari Pengadilan Agama Palembang menunjukkan bahwa pasangan berusia 56 tahun ke atas tetap berada dalam kondisi rentan terhadap perceraian. Artikel ini bertujuan untuk menganalisis tipologi penyebab perceraian usia lanjut dan mengkaji konstruksi argumentasi hukum yang digunakan oleh hakim muslim dalam memutus perkara, melalui pendekatan sosio-legal yang mengintegrasikan studi lapangan dengan analisis yurisprudensi terhadap 56 putusan Pengadilan Agama Palembang tahun 2022. Hasil penelitian menunjukkan bahwa perceraian pada usia lanjut tidak terjadi secara tiba-tiba, melainkan merupakan akumulasi konflik jangka panjang yang bersifat struktural, termasuk kekerasan domestik, subordinasi ekonomi, serta ketimpangan dalam relasi seksual dan emosional. Temuan ini juga memperlihatkan bahwa argumentasi hukum hakim muslim dalam memutus perkara tidak sepenuhnya bersifat netral, tetapi turut mencerminkan internalisasi norma sosial dan struktur relasi kuasa yang terlembaga dalam sistem peradilan. Dengan demikian, artikel ini menegaskan bahwa perceraian usia lanjut bukan sekadar kegagalan relasi personal, melainkan perlu dipahami sebagai manifestasi dari ketidaksetaraan gender yang beroperasi dalam dua arena utama: domestik dan institusional. Oleh karena itu, diperlukan reformulasi pendekatan hukum Islam dan penguatan sistem peradilan agama yang lebih responsif terhadap dimensi ketimpangan struktural berbasis gender dalam konteks perceraian lansia.]